Modeling energy consumption role on the productivity of coastal community-based fishery business activities in the small islands region - Glenty Benoni Aminadap Somnaikubun (Sangia Publishing, 2021)
The geographic condition of the archipelago and the inter-regional connectivity within the Kei Islands is still minimal due to the support of infrastructure and natural conditions, causing the sustainability of coastal area-based businesses, particularly capturing fisheries and mariculture fisheries are potentially be disrupted. This research aims to analyze the factors that hamper the productivity of fishing businesses in coastal areas concerning energy consumption and availability to support the business being run. This research used the PLS method, where data were collected from February 2019 to August 2020 in 40 villages with 414 respondents. The results show that consumption has a significant and positive relationship to access and availability on fisheries business productivity. This study also shows that various flow patterns and relationship patterns between variables can affect fisheries business productivity. The implications of this result can be an input for policymakers in this region to better support and maintain the availability of energy to maintain the sustainability of the business productivity of coastal communities in this region.